If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3 + -1x) + 9x = 26 (3 * 7 + -1x * 7) + 9x = 26 (21 + -7x) + 9x = 26 Combine like terms: -7x + 9x = 2x 21 + 2x = 26 Solving 21 + 2x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 2x = 26 + -21 Combine like terms: 21 + -21 = 0 0 + 2x = 26 + -21 2x = 26 + -21 Combine like terms: 26 + -21 = 5 2x = 5 Divide each side by '2'. x = 2.5 Simplifying x = 2.5
| 8(3x+2)=4(5x+1) | | 2(4x-5)= | | 7x+6=2(3x+2) | | 4(5x-1)=3(4x+12) | | 2(3x+5)-3=16 | | 3(8x+2)-4x=36 | | 3x+4(2x-3)=10 | | 9x+2(x+7)=36 | | 7(5x-2)-8(4x+1)=5 | | 6(4X+3)-9(2X+1)=21 | | 3(3X+5)+2(3X-7)=19 | | 3(9X+4)=5(5X+4) | | 5(7X-1)=11(3X+2) | | 100-96=31y-35y | | 6(3X+2)=4(4X+7) | | -14m+8m=6-60 | | 9p+5q=63 | | 0=-9t | | 3(X+0.3)=1-X | | 3t+9t=20-10+26 | | 3x+14x-5=0 | | 7(a+3)=49 | | 3(a-1)=2(a+1) | | 13-13=2w-w | | -97-10x=9x+7 | | 7=7c-7 | | 3x+7=-45+10x | | x-9x=80 | | 4e-9=3 | | 3-0.8X=7-X | | x-w=y | | 2-0.66X=5-X |